E-health roadmap for COVID-19 vaccine coverage in Iran - Elham Maserat; Leila Keikha; Somayeh Davoodi; Zeinab Mohammadzadeh (BMC, 2021)
Abstract Background Vaccination is the effective and long-term pharmacological solution to deal with COVID-19. Information technology (IT) and electronic immunization can be effective in accelerating and improving vaccine coverage. The aim of this paper is to develop multi-dimensional framework of e-health roadmap to response Covod-19 pandemic and examine the role of IT for improving vaccine distribution in Iran. Methods The study methodology was based on a two-stage Delphi method which included literature studies at the beginning. Key steps in creating a roadmap in this study include definition, development and evaluation. The initial conceptual model was developed after literature review. Proposed roadmap was reviewed and evaluated in two stages based on the Delphi method by experts in the fields of E-health. Results In the e-health roadmap model, 14 stages of vaccine distribution were presented in three phases of vaccination and then were determined the type of technology in each phase. The 4 conceptual models were approved based on the two stages Delphi approach in a survey of 14 e-health experts. In the second phase of the Delphi process, the selected items were sent back to the specialists to verification. Then e-health roadmap was confirmed by experts and was finalized the approved model. Conclusions The technology-based roadmap is one plan in the form of a transfer strategy that aligns goals with specific technical solutions and helps to meet them. This roadmap empowers decision makers to decide on alternative paths and achieve goals.